Indifference : On the Praxis of Interspecies Being - Dave, Naisargi N. (Naisargi Nitin), 1975- (Book collections on Project MUSE., 2023)
"Through ethnographic fieldwork with animal healers, animal activists, farmers, laborers, transporters, and animals themselves, Naisargi N. Dave illuminates an interspecies relationality premised on indifference: that is, premised on mutual regard rather than curiosity, love, fascination, desire, or animus. Building on the work of Edouard Glissant, Dave argues against the invasiveness and whiteness of curiosity in favor of indifference. In this formulation of indifference, it becomes a way to show respect for other creatures and their privacy and allows us to exist in difference from one another without intrusively gazing upon the differences of the other. The chapters span settings from animal shelters, slaughterhouses, dairy farms, city streets, and poultry factories to show how human-animal relations manifest through care and violence, but find promise in moments of indifference. Indifference describes both a mode of relationality in the world and a scholarly approach: seeking what is possible when we approach ethico-political explanations with indifference rather than commitment or antagonism"--